Structural, electronic, mechanical, optical and magnetic properties of RhNbZ (Z = Li, Si, As) Half-Heusler compounds: a first-principles study - Adem Beriso Bejo; Megersa Wodajo Shura; Kumneger Tadele; Mesfin Asfaw Afrassa; Fekadu Tolessa Maremi (Materials Research Express)
Structural, mechanical, electronic, optical and magnetic properties of the cubic RhNbZ (Z = Li, Si, As) half-Heusler compounds is reported using density functional theory (DFT) as implemented in quantum espresso simulation package. Structurally, the compounds are most stable when they are in type I atomic arrangement. Studies of mechanical properties indicate that all the three compounds are ductile in nature and mechanically stable. Calculations of electronic band structure and density of states (DOS) affirm that RhNbSi is a semi-conductor with an indirect band gap of 0.662 eV and 1.0095 eV from generalized gradient approximation (GGA) and GGA+U approaches respectively, where U is Hubbard parameter, RhNbLi has metallic property under both GGA and GGA+U approaches whereas RhNbAs has metallic nature under GGA prediction but it has half-metallic property under GGA+U approach, a property which is essential for spintronic applications. Optical parameters such as dielectric function, reflectivity, refractive index, extinction coefficient, absorption coefficient, optical conductivity and electron energy loss were estimated in the photon energy range of 0–40 eV. Results from these properties calculations reveal that both absorption coefficient and optical conductivity have maximum values whereas electron energy loss has minimum value in the lower energy ranges which show that the materials under our study can be considered as potential candidates for optoelectronic applications. From magnetic property calculations, RhNbSi is predicted to be nonmagnetic material but RhNbLi and RhNbAs have magnetic nature.